2008
DOI: 10.1590/s1413-86702008000100009
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic markers of symptomatic congenital cytomegalovirus infection

Abstract: The objective of this research was to identify maternal and fetal characteristics as prognostic markers of congenital cytomegalovirus (CMV) infection. This is a descriptive study of 13 cases of congenital CMV infection referred to Institute de Puericulture et Perinatologie de Paris (IPP) from January 2005 to October 2006. Amniotic fluid puncture was performed to research CMV polimerase chain reaction (PCR). Cordocentesis and cord blood samples at delivery were also analyzed to determinate fetal platelets count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
1
28
2
1
Order By: Relevance
“…31,32 More recently, the availability of quantitative PCR-assays has increased interest in the potential role of viral load in predicting disease outcome, development of hearing loss and monitoring response to antiviral therapy in congenital HCMV infection; however, in practice many questions are still open. 2 Revello et al, and Romanelli et al, have not found association between the viral load and the prediction of the symptom in the newborns or the appearance of sequelae 33,34 which is in agreement with the lack of associations also reported in the present study. However, the 2 newborn with retarded intrauterine growth and severe jaundice showed high viral load (Ͼ1000 copies/L), but a statistically significant association was not found since the sample size is small.…”
Section: Discussionsupporting
confidence: 92%
“…31,32 More recently, the availability of quantitative PCR-assays has increased interest in the potential role of viral load in predicting disease outcome, development of hearing loss and monitoring response to antiviral therapy in congenital HCMV infection; however, in practice many questions are still open. 2 Revello et al, and Romanelli et al, have not found association between the viral load and the prediction of the symptom in the newborns or the appearance of sequelae 33,34 which is in agreement with the lack of associations also reported in the present study. However, the 2 newborn with retarded intrauterine growth and severe jaundice showed high viral load (Ͼ1000 copies/L), but a statistically significant association was not found since the sample size is small.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to what physicians might anticipate, the viral load in the amniotic sac does not seem to be a reliable predictor of neonatal clinical outcome [46,47]. Furthermore, data on the usefulness of CMV specific IgM and CMV-DNA concentrations in fetal umbilical cord blood as prognostic parameters are conflicting [41,48,49]. …”
Section: Diagnosis Of Primary Maternal and Fetal CMV Infection And Prmentioning
confidence: 99%
“…Infected women often present with nonspecific signs and symptoms, but the majority are asymptomatic [6]. Approximately 10% of newborns show symptoms at birth [1, 35] but this increases to 20–30% if their mothers were infected in the first trimester [7]. There is a 30% mortality in the affected infants and 90% will have long-term neurological impairment [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of newborns show symptoms at birth [1, 35] but this increases to 20–30% if their mothers were infected in the first trimester [7]. There is a 30% mortality in the affected infants and 90% will have long-term neurological impairment [4, 5]. Of the asymptomatic neonates, 10% will develop permanent sequelae, including hearing loss and mental retardation [1, 35].…”
Section: Introductionmentioning
confidence: 99%